Entrapment of α-Amylase in Agar Beads for Biocatalysis of Macromolecular Substrate. (15th September 2014) - Sharma, Manu; Sharma, Vinay; Majumdar, Dipak K.
Abstract : Attempts have been made to optimize immobilization parameters, catalytic property, and stability of immobilized α -amylase in agar. The work compares natural entrapment efficiency of agar with the ionotropically cross-linked agar hydrogel, with the advantage of easy scale-up and cost and time effectiveness. Beads prepared with 3% (w/v) agar and 75 mM calcium chloride and hardened for 20 minutes were selected for further studies on the basis of entrapment efficiency (80%) and physical stability. Following entrapment, pH and temperature optima of enzyme were shifted from 6 to 6.5 and 50 to 55°C, respectively. Michaelis constant (K m ) for both free and entrapped enzymes remained the same (0.83%) suggesting no change in substrate affinity. However, V max ⁡ of entrapped enzyme decreased 37.5-fold. The midpoint of thermal inactivation for entrapped enzyme increased by 8 ± 1°C implying its higher thermal stability. The entrapped enzyme in calcium agar bead had an Ea value of 27.49 kcal/mol compared to 17.6 kcal/mol for free enzyme indicating increased stability on entrapment. Half-life of enzyme increased 2.2 times after entrapment in calcium agar at 60°C indicating stabilization of enzyme. The reusability of beads was size dependent. Beads with diameter <710 μ m were stable and could be reused for 6 cycles with 22% loss in activity.